Issues associated with welding and surfacing of large mobile mining equipment for use in oil sands applications. (August 2015) - Barnes, N.; Joseph, T.; Mendez, P. F.
Abstract : Welding for large mobile mining equipment commonly used in the oil sands mining industry represents a unique aspect of the construction and mining heavy equipment industries. Low volume, high production capacity dominates, differing from the high volume, low production typical of the on-highway cartage automotive industry. The use of robotic welders is increasing but remains predominantly avoided due to the high cost associated with fixturing and positioning of large structural components, compounded by tolerance concerns. The main issues facing weld performance are fatigue and wear. A large portion of the ultraclass large mobile mining equipment industry focuses on fast field repair techniques, dominated by shielded metal arc welding, while in shop repairs, gas metal arc welding remains the preference.